Territory planning and tourism development in the coastal zone of Ukraine - Panchenko, T. (KNUCA, 2019)
The Black Sea Region of Ukraine with the length of 2,8 thousand km can be identified as one of the most long-range regions in regard to the sustainable tourism development. The potential opportunities of the possible tourism development and improvement can be caused by the following main factors: incomplete level of the development of tourism resources; attractiveness for the population of such regions as East Europe, North and Central Asia that have transport connection and traditionally use the Black Sea coast for summer rest without language barrier; enlargement of the tourism field for the tourists from the countries of Central and West Europe; developing of the quality of the tourism service as a result of the realization of the privatization of the tourist complexes; improvement of the environmental safely level that is already observed and can be continued as a result of the implementation of the environmental measures; development of the transport system, improvement of the access and visa regime; difference between the costs for tourist services. The Law of Ukraine "On Tourism", established the legislative preconditions for tourism transformation. Also provided the essential change of the governmental scheme in the field of tourism with the aim so approach its formation to the one of the one of the priorities in the branch of economics. At the same time the real problems and constraints exist which restrain the sustainable tourism development in the Ukrainian, part of the coastal zone. There is a necessity for the development of some parts of the tourism services which are the obligatory components of the market economy system and which formerly were not developed or were solved without taking into account economic measures. They are: the establishment of the marketing system for the provisions of the tourism activities, including the establishment of the sale system, advertisement, arrangement of the services structure in accordance to the requirements, certification of the tourist complexes in regard to the world service level; development of the tourist infrastructure, provision of the necessary, information about the quality of environment and value of recreated resources. There is a need to conduct the environmental sanitation of the tourist complexes on the base of their privatization.
Keywords: territory planning; coastal zone; tourism development; description of the Azov-Black Sea region